From Fatwa to Bureaucracy: How Indonesian Penghulu Negotiate Islamic Law and State Regulations on Post-Divorce Marriages (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2025)
The state policy prohibiting men from remarrying during their ex-wife’s iddah period has generated varied responses among marriage registrars (penghulu). Within the framework of legal pluralism, this article analyzes the tension between classical fiqh and state regulation, as well as its institutional implications. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data were analyzed using condensation, presentation, and conclusion drawing, while source triangulation was used to ensure validity. The findings reveal different interpretations among penghulu, rooted in the enduring authority of classical fiqh as a normative reference amid the presence of state law. In practice, these differences have resulted in three implementation patterns: (1) partial application of the Circular Letter, (2) full implementation, and (3) complete rejection. This phenomenon illustrates that in the realm of Islamic family law, state regulation has not fully displaced Islamic legal authority as the primary reference in religious institutional practice.